Limitierte Stufenflexibilität - Helmut Lipfert (Kredit und Kapital, 1970)
Limited Flexibility A Possible Solution to the Exchange Rate Problem The monetary system created at Bretton Woods ın 1944 did not provide an optimal solution to the problem of adjusting parities. Since freely floating exchange rates scarcely have a chance of realization owing to their feared disintegrating effect, only a reform "of small steps" can be considered. In such a reform the three following aspects must be taken into account: 1. individual economic interest in the calculability of the exchange rate risk; 2. national economic interest in exchange rate flexibility in order, if necessary, to escape as far as possible from the influences of other national economies; 3. supranational interest in unjeopardized integration so that general prosperity can improve unhindered. These demands on a reform are satisfied by "limited" flexibility, under which system the most important members of the IMF untertake 1. not to adjust the parity more than 2 % per year, 2. to broaden (e. g. to double) the band. In this way parity adjustments could become a normal "unpolitical" monetary instrument such as, say, bank rate policy. Since the exchange rate can fluctuate freely within the broader band, the parity adjustment would be of confirmatory character only, the band may merely be shifted. An important benefit of this "limited" system consists in making the exchange risk calculable for the exporting and importing economy and sparing it extreme situations in which excessive risks of loss due to parity changes have to be accepted or excessive prices have to be paid for exclusion of those risks.
Keywords: 330